2015
DOI: 10.3892/mmr.2015.4196
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress biomarkers and paraoxonase 1 polymorphism frequency in farmers occupationally exposed to pesticides

Abstract: Abstract. Previous evidence has demonstrated that chemical classes of pesticides, including organophosphates (OP), can induce oxidative stress in exposed workers. The resulting increase in free radicals causes damage to biological macromolecules, and promotes the formation of novel compounds, including advanced glycation end products (AGE) and advanced oxidation protein products (AOPP). The present study aimed to evaluate the common genetic polymorphisms of the paraoxonase 1 (PON1) gene in a group of 55 farmer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 34 publications
0
27
1
4
Order By: Relevance
“…In addition, we found that also the maternal PON1 Q192R genotype affected the associations. Mothers carrying the R‐allele may detoxify some pesticides more slowly and have reduced antioxidative capacity to protect against lipid oxidation, resulting in a more unhealthy metabolic profile (Aviram et al ., ; Macharia et al ., ; Costa et al ., ). This might result in a more adverse intrauterine environment affecting metabolic programming.…”
Section: Discussion With Conclusionmentioning
confidence: 97%
“…In addition, we found that also the maternal PON1 Q192R genotype affected the associations. Mothers carrying the R‐allele may detoxify some pesticides more slowly and have reduced antioxidative capacity to protect against lipid oxidation, resulting in a more unhealthy metabolic profile (Aviram et al ., ; Macharia et al ., ; Costa et al ., ). This might result in a more adverse intrauterine environment affecting metabolic programming.…”
Section: Discussion With Conclusionmentioning
confidence: 97%
“…Pesticides are varied in terms of the structure and usage of chemical substances, their main purpose being to provide protection against pests [6]. The use of pesticides causes environmental pollution and accidental exposure of certain groups of people to their harmful effects [7].…”
Section: Discussionmentioning
confidence: 99%
“…PON1 activity varies significantly among individuals, and several molecular variants of this enzyme are recognised. Pesticide exposure and the consequent oxidative stress both have an impact on PON1 gene polymorphisms (60), and research has indicated that an epigenetic mechanism may be responsible for these alterations (61,62). …”
Section: Epigeneticsmentioning
confidence: 99%